Protocolo assistencial sobre prevenção e manejo com lesão por pressão de pacientes oncológicos em cuidados paliativos - MACÊDO, Winnie Taíse Pena (Universidade Federal do Pará, 2023)
Introduction: When faced with a patient with skin lesions at the end of life, decision-making by nurses can be challenging, either because of the uncertainty of the goals of care, or because of concerns about generating anguish and discomfort for the patient and their families. It is not uncommon to find behaviors that diverge regarding skin care at the end of life, thus, there is a need to equip health professionals and thus harmonize the conduct of their care. Objectives: To analyze the information on prevention and care of pressure injuries, necessary for patients in oncological palliative care in the hospital context, which can compose a care protocol to be constructed and validated. Method: this is a methodological study developed in three stages: literature review; technological production and semantic validation, with a qualitative quantitative approach. It was performed at Ophir Loyola Hospital. The sample was intentional and the population consisted of nurses who met the eligibility criteria. The nurses were introduced to the protocol, so that they could handle it and describe their impressions, in addition to the assessment instrument, which aimed to verify the agreement between the participants using the Likert Scale, and for quantitative validation, the CVI was used. Results: The first stage of the results was the construction of an Integrative Literature Review. The second step was the construction of the protocol, based on evidence from the RIL, as well as supporting its recommendations through a guideline. The third step was the semantic validation, which aimed to verify the understanding, relevance and possible need to modify the protocol items. The population consisted of 9 nurses, most aged between 35-45 years, lato sensu postgraduate, worked in care, had experience in pressure injuries in the palliative care scenario for more than 10 years. As for semantic validation, the protocol presented a CVI of 0.97, being considered validated by the target audience, according to the proposed methodology. Discussion: It is noteworthy that the target audience of this study validated the protocol with high values, with most subitems having maximum agreement, which reflects an excellent level of protocol acceptability. Thus, a new round of validation was not necessary, as the individual CVI of each subitem was greater than 0.80. Conclusion: It is expected that this protocol can be used in different scenarios that provide health care for this fragile and vulnerable population. It is also expected that this instrument can provide tools for nursing professionals and positively impact the quality of life of cancer patients in palliative care with pressure injuries, especially those who go through their final stage of life